Development of multiplex real-time PCR for simultaneous detection of SARS-CoV-2, CCoV, and FIPV - Liu, Yan; Zhu, Zhen; Du, Jige; Zhu, Xiaojie; Pan, Chenfan; Yin, Chunsheng; Sun, Weidong (Frontiers in Veterinary Science, 2024)
Coronaviruses, including severe acute respiratory syndrome coronavirus 2(SARS-CoV-2), canine coronavirus(CCoV), and feline infectious peritonitis virus(FIPV)， have the potential for interspecies transmission. These viruses can be present in complex environments where humans, dogs, and cats co-exist, posing a significant threat to both human and animal safety. In this study, we developed a novel multiplex TaqMan-probe-based real-time PCR assay for the simultaneous detection and differentiation of SARS-CoV-2, CCoV, and FIPV. Specific primers and TaqMan fluorescent probes were designed based on the N region of SARS-CoV-2 and FIPV, as well as the S region of CCoV, which demonstrated a remarkable sensitivity and specificity toward the targeted viruses, as few as 21.83, 17.25 and 9.25 copies/μL for SARS-CoV-2, CCoV and FIPV, respectively. The standard curve constructed by the optimized method in our present study showed a high amplification efficiency within or near the optimal range of 91 to 116% and R(2) values were at least 0.95 for the above-mentioned coronaviruses. A total of 91 samples, including six plasmid mixed mock samples, four virus fluid mixing simulated samples, and 81 clinical samples, were analyzed using this method. Results demonstrated strong agreement with conventional approaches.By enabling the simultaneous detection of three viruses, this method enhances testing efficiency while decreasing costs. Importantly, it provides a valuable tool for the prevalence and geographical distribution of suspected and co-infected animals, ultimately contributing to the advancement of both animal and public health.